Inventory and review of the Mio–Pleistocene São Jorge flora (Madeira Island, Portugal): palaeoecological and biogeographical implications. (26th January 2018) - Góis-Marques, Carlos A.; Madeira, José; Menezes de Sequeira, Miguel
Abstract : The occurrence of plant fossils on Madeira Island has been known since the mid-nineteenth century. Charles Lyell and George Hartung discovered a leaf bed rich in Lauraceae and fern fossils at São Jorge in 1854. The determinations were controversial but a full review was never performed. Here we propose possible geological settings for the fossiliferous outcrop, and present an inventory and a systematic review of the surviving specimens of the São Jorge macroflora. The São Jorge leaf bed no longer outcrops due to a landslide in 1865. It was possible to establish the two alternative volcano-stratigraphical settings in the sedimentary intercalations from the Middle Volcanic Complex, ranging in age from 7 to 1.8 Ma. The descriptions of Heer (1857 ), Bunbury (1859 ) and Hartung & Mayer (1864 ) are reviewed based on 82 surviving specimens. From the initial 37 taxa, we recognize only 20: Osmunda sp., Pteridium aquilinum, Asplenium cf. onopteris, aff. Asplenium, cf. Polystichum, cf. Davallia, Woodwardia radicans, Filicopsida gen. et sp. indet. 1 and 2, Ocotea foetens, Salix sp., Erica arborea, cf. Vaccinium, Rubus sp, cf. Myrtus, Magnoliopsida gen. et sp. indet. 1 to 3, Liliopsida gen. et sp. indet. 1. Magnoliopsida gen. et sp. indet. 4 is based on one previously undescribed flower or fruit. The floristic composition of the São Jorge fossils resembles the current floristic association of temperate stink laurel ( Ocotea foetens ) forest, suggesting a warm and humid palaeoclimate and indicating that laurel forests were present in Macaronesia at least since the Gelasian, a time when the palaeotropical geofloral elements were almost extinct in Europe.